Peran Gender Kontemporer di Indonesia - Perubahan dan Keberlanjutan: Studi Pustaka - Nugraha, Sumedi P.; Susilastuti, Dewi Haryani (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
This study aims to find out the way gender socialization affects the young people’s perception on men and women roles. This paper uses state-supported gender roles in the Soeharto era as a benchmark for gender ideology today. The government of Soeharto marked a pivotal moment in the development of the expected roles of men and women both in the public and private areas. The aims of this paper are: (1) to explore whether gender roles in Indonesia have shifted from the Soeharto era to the present, (2) to examine what messages are conveyed by TV, schools and social media as agents of socialization, and (3) to look at young people's perceptions of "ideal roles” for men and women. The data from this paper are from journal articles, books and dissertations written in English taken from Proquest database by using the specific key words. Article searches were also conducted on the internet with the same keywords, both in English and in Indonesian. This literature review shows that inspite of various progress in the educational and political sectors, contemporary gender roles in Indonesia are relatively the same as traditional gender roles in the Suharto’s era. Young people, both men and some women, consider jobs in the public area and leadership positions as male domains. On the other hand, domestic work is considered as women's work, even though women work full time outside the house. The discrepancy between social expectations and the reality of everyday life often causes the double burden and the stress among women.